The Strategic Role of the Kitchen in Supporting Food and Beverage Operations at Melva Balemong Hotel & Resort - Octavianti Paramita; Chandra Wasana; Velisya Cahya Aulia; Rindhani Safra Damayanti; Keyla Laksmi Chantika; Rizki Lestari; Queen Tauhida Rabbani (Universitas Negeri Semarang, 2026)
This study aims to analyze the strategic role of the kitchen in supporting Food and Beverage operations at Melva Balemong Hotel & Resort. As a key contributor to service quality and revenue, the kitchen serves as the central production unit responsible for food quality, consistency, safety, and operational efficiency. Using a qualitative descriptive approach through a literature review of seventeen scientific articles, this study examines kitchen operations, human resource management, standard operating procedures, hygiene and sanitation, product innovation, and service quality in the hospitality industry. The findings reveal that effective kitchen operations depend on employee competence, adherence to standard operating procedures, hygiene and sanitation practices, adequate equipment, and food product innovation. The kitchen also plays a significant role in enhancing customer satisfaction through product quality, breakfast services, pastry and bakery production, and menu differentiation. The study concludes that the kitchen is not merely a food production area but a strategic component that supports service quality, operational effectiveness, customer satisfaction, and hotel competitiveness. Therefore, continuous improvements in human resources, operational systems, and kitchen facilities are necessary to sustain the success of Food and Beverage operations at Melva Balemong Hotel & Resort.Keywords: Kitchen Operations, Food and Beverage, Hotel Management, Service Quality, Customer Satisfaction